Manifest system for management of non-hazardous industrial solid wastes: results from a Tianjin industrial park. (1st October 2016) - Zhang, Mo; Wang, Yanhui; Song, Yuyan; Zhang, Tao; Wang, Junfeng
Abstract: Industrial parks pose a significant challenge in industrial solid waste management (ISWM) due to the large quantity of waste they generate. The manifest system, a tool currently used mainly for the management and tracking of hazardous waste, has been employed in a pilot project on non-hazardous industrial solid waste (NHISW) in the Tianjin Economic-Technological Development Area (TEDA). This paper focuses on the implementation of a non-hazardous industrial solid waste manifest system (NHISWMS) in TEDA, which aims to track the NHISW transfer path, and accurately acquire detailed information on each specific company. Using a total of 1456 manifests from 25 tenant companies over one year of research, this paper analyzes the information generated on waste generation, transfer and disposal. The results show that more than 50% of NHISW leaves TEDA but remains in Tianjin province, and more than 65% of NHISW is utilized or disposed by only one waste receiver. The research concludes that the manifest is an effective instrument for analyzing NHISW characteristics and identifying connections between waste handlers in order to establish a waste recycling industry chain. The experiences and methods from this case study are highly applicable to other industrial parks seeking to improve their waste management. Highlights: A manifest system can track non-hazardous industrial waste in an industrial park. The manifest is an effective tool to identify volume and type of waste generated. The manifest allows analysis of the flow of waste inside and outside the park. The manifest enables improved waste management.